Improving RGB Image Consistency for Depth-Camera based Reconstruction through Image Warping - Reyes-Aviles, Fernando; Fleck, Philipp; Schmalstieg, Dieter; Arth, Clemens (Journal of WSCG, 2020)
Indoor reconstruction using depth camera algorithms (e.g., InfiniTAMv3) is becoming increasingly popular. Simple reconstruction methods solely use the frames of the depth camera, leaving any imagery from the adjunct RGB camera untouched. Recent approaches also incorporate color camera information to improve consistency. However, the results heavily depend on the accuracy of the rig calibration, which can strongly vary in quality. Unfortunately, any errors in the rig calibration result in apparent visual discrepancies when it comes to colorization of the 3D reconstruction. We propose an easy approach to fix this issue for the purpose of image-based rendering. We show that a relatively simple warping function can be calculated from a 3D checkerboard pattern for a rig with poor calibration between cameras. The warping is applied to the RGB images online during reconstruction, leading to a significantly improved visual result.